Korelasi Salat Dengan Fahsha' dan Mungkar Dalam Perspektif Al-Qur'an (Studi QS Al-Ankabut 45) - Nurfadliyati, Nurfadliyati (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2020)
This article aims to explore causality Qs.Al-Ankabut: 45 "Prayer prohibits immorality (fahsha') and wrongdoing (munkar)", There is a cause and effect if prayer is performed, it will prevent the prayer from immorality and wrongdoing. However, Quraish Shihab said that this verse was the subject of discussion and questions of the ulama, especially after seeing many who prayed but the prayer he did not need from immorality and wrongdoing. This is what encourages the author to study this verse, how the meaning ofÂ  Islamic prayer in the Qur'an, and what is the meaning immorality (Fahsha') and wrongdoing (munkar) in the Qur'an and how to correlation salat with immorality and wrongdoing. The method is library research, which is research conducted to collect and analyze data sourced from libraries, in the form of books, scientific magazines and various library sources which are used as research references. With data collection and documentation techniques, as for the proposed are various literacy works relating to the subject matter in this study. The results of the authors find that prayers that prevent acts of immorality and wrongdoing are prayers that are done sincerely, done according to the conditions, in harmony, and done with great solemnity, a submissive heart,keeping the prayers and being done continuously and doing sunnah prayers recommended. If the prayer is done in such a way, then the prayer can deter and prevent those who do it from immorality and wrongdoing.Â